2016
DOI: 10.1186/s40816-016-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of Tonsilgon® N in the treatment of recurrent upper respiratory tract infections in children: a non-interventional study in Russia

Abstract: Background: Acute upper respiratory tract infections (ARI) in children are quite common and often recurrent. Overuse of antibiotics must be avoided, and thus herbal remedies are a useful therapeutic option, as most ARIs can be treated without antibiotics. The aim of this observational study was to demonstrate the effectiveness and tolerability of the herbal combination preparation Tonsilgon® N in Russian children aged 2-11 years in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Moreover, the immunomodulatory effects of the medicine have been shown, and these refer to stimulation of nK cell activity by 150%, increased cytolytic activity and interferon production, as demonstrated in an in vitro study of human tonsil cells [19]. Clinical studies: Clinical studies have confirmed the therapeutic efficacy of the medicine in relieving the course of infection, as well as shortening its duration [23][24][25]. the controlled clinical trials conducted to date are not sufficient to support the well-established use of the medicinal product.…”
Section: Onion Bulb (Allii Cepae Bulbus)mentioning
confidence: 94%
“…Moreover, the immunomodulatory effects of the medicine have been shown, and these refer to stimulation of nK cell activity by 150%, increased cytolytic activity and interferon production, as demonstrated in an in vitro study of human tonsil cells [19]. Clinical studies: Clinical studies have confirmed the therapeutic efficacy of the medicine in relieving the course of infection, as well as shortening its duration [23][24][25]. the controlled clinical trials conducted to date are not sufficient to support the well-established use of the medicinal product.…”
Section: Onion Bulb (Allii Cepae Bulbus)mentioning
confidence: 94%
“…Overall compliance was high (88.2%). This leads to the conclusion that BNO 1030/1035 is a safe and effective option for the treatment of acute respiratory viral infections in children (aged 2-11 years) which reduces the duration of ARVI symptoms [16].…”
Section: Sinupret® Extract: a History Of Success (Prof Claus Bachertmentioning
confidence: 99%
“…Furthermore, cough can be targeted through specific antitussive medicines [10][11][12]. A number of herbal and traditional remedies also exist to help alleviate symptoms including honey as an antitussive agent [13], saline solutions for nasal congestion and throat irritation [14], vitamins, mineral supplements and remedies purported to boost immune function [12,[15][16][17] and topical vapour rub ointments containing menthol, camphor and eucalyptus, which release therapeutic vapours aimed at reducing cough and congestion and making breathing easier [18].…”
Section: Introductionmentioning
confidence: 99%